Arabs and the Qur’an In the Context of A Non-Lıterate Socıety - Tuncer, Faruk (South Asian Journal of Religion and Philosophy (SAJRP), 2024)
Despite the revelation of the Qur’an in the 7th century AD in the Hijaz region, the condition of literary practices still carries some uncertainties. New studies are needed, and detailed investigations are required. Although it is known that writing began in Mecca with the onset of the revelation of the Qur’an, records related to this early phase of the Meccan period are quite limited and scarce compared to records from the Madina period. The main reason for this is closely related to the fact that the Meccans of the 6th century were a “non-literate society” and the inadequacy of information in Islamic sources in this regard. With the increase in modern anthropological and archaeological data, there is a need to analyze and reinterpret existing data. In this article, we attempt to present such a perspective by emphasizing the need to interpret existing data with a new approach.